Front-Line Therapy for Elderly Chronic Lymphocytic Leukemia Patients: Bendamustine Plus Rituximab or Chlorambucil Plus Rituximab? Real-Life Retrospective Multicenter Study in the Lazio Region - Autore, Francesco; Innocenti, Idanna; Corrente, Francesco; Del Principe, Maria Ilaria; Rosati, Serena; Falcucci, Paolo; Fresa, Alberto; Conte, Esmeralda; Limongiello, Maria Assunta; Renzi, Daniela; De Padua, Laura; Andriani, Alessandro; et al. (Frontiers in Oncology, 2020)
Previous studies investigated the efficacy and the safety of bendamustine (B) vs. chlorambucil (Chl) associated with rituximab (R) in fludarabine-ineligible patients with treated and untreated chronic lymphocytic leukemia (CLL). We conducted a retrospective multicenter study in the Lazio region to further evaluate and compare the efficacy and the toxicity of Chl-R and B-R regimen in CLL patients over the age of 65. We enrolled 192 untreated CLL patients: 111 treated with B-R and 81 with Chl-R. The overall response rates (ORR; 93.6% in B-R and 86.5% in Chl-R) were not statistically different between the two groups, such as progression-free survival (PFS), time to retreatment (TTR), and overall survival (OS). The B-R group showed a higher hematological (p = 0.007) and extra-hematological (p = 0.008) toxicity. When comparing the toxicities according to age, we noted that the extra-hematological toxicity was higher in patients over the age of 75 who were treated with B-R than those treated with Chl-R (p = 0.03). This retrospective study confirms the feasibility of B-R and Chl-R in elderly untreated CLL patients. Currently, patients who are over 75 and unfit are usually treated with Chl-R. This scheme allows achieving the same ORR, PFS, TTR, and OS when compared with B-R because of hematological and extra-hematological toxicities due to B, in which a greater dose reduction has been shown in comparison to Chl.